Investigating the effect of polymer-modified graphene oxide coating on RO membrane fouling. (October 2022) - Ashfaq, Mohammad Y.; Al-Ghouti, Mohammad A.; Zouari, Nabil
Abstract: The development of novel reverse osmosis (RO) membranes resistant to multiple types of fouling is a need to secure clean water production and meet rising water demands. In this paper, the RO membrane surface-functionalized with antibacterial graphene oxide (GO) and antiscalant maleic acid was prepared and tested. The polymerization of maleic acid on the GO functionalized RO membrane was achieved using microwave radiation. The membrane surface characterization showed a decrease in membrane surface roughness from 74.7 nm to 69.0 nm and an increase in membrane hydrophilicity as the contact angle decreased from 41.7 ± 4.5 0 to 22.0 ± 1.1 0 . The modified membrane was tested against inorganic scaling and biofouling, and the results demonstrated that the modified membrane has improved resistance to multiple fouling types as compared to the unmodified RO membrane. When tested in the presence of calcium sulfate scaling solution (inorganic fouling), the normalized permeate flux was found to be stable at 0.91 and 0.95 for 0.01 and 0.02 wt% maleic acid-modified RO membranes, respectively. Moreover, the modified membranes also demonstrated bacteriostasis rates of 96.1 %–97.1 % showing their anti-bacterial characteristics. Both types of membrane fouling (inorganic and biofouling) were also studied simultaneously, and the results showed that the RO membranes with dual capabilities can inhibit both mineral formation and biofilm growth concurrently. Graphical abstract: Unlabelled Image Highlights: Biofouling and Inorganic fouling co-exist, interact, and complicate the membrane fouling. Reverse osmosis membrane was surface coated with polymer-modified graphene oxide to reduce fouling. The coated RO membranes demonstrated high hydrophilicity and surface smoothness. Against inorganic fouling, the flux remained stable for 6 h, while the bacterial growth rate was reduced by 97 %. The modified membranes were able to inhibit both inorganic fouling and biofouling.